Arquipélago. - Fundação Calouste Gulbenkian, Lissabon (Lissabon : Fundação Calouste Gulbenkian, 1985)
Léon, Ana ; Croft, José Pedro ; Cabrita Reis, Pedro ; Calapez, Pedro ; Carvalho, Rosa ; Sanches, Rui
Arquipélago, Fundação Calouste Gulbenkian, Lissabon, Novembro 1985
boek